Effect of long-term inorganic nitrate administration on myocardial ischemia-reperfusion injury in ovariectomized rats - Jeddi, Sajad; Yousefzadeh, Nasibeh; Zarkesh, Maryam; Kashfi, Khosrow; Ghasemi, Asghar (Frontiers in Pharmacology, 2024)
Menopause is associated with reduced nitric oxide (NO) bioavailability and lower tolerance against myocardial ischemia-reperfusion (IR) injury. This study investigated whether longterm nitrate administration provides resistance against myocardial IR injury in ovariectomized (OVX) rats. Method: After ovariectomy, female rats were assigned to the OVX and the OVX+nitrate groups (n=14/group); the latter group consumed nitrate (100 mg/L) for 9 months. At month 9, each group was divided into two subgroups (n=7/subgroup), of which one subgroup was exposed to myocardial IR (IR + hearts) and the other was not exposed (IR -hearts). The hearts of rats were isolated, and NO metabolite (NOx), oxidative stress indices, and mRNA expressions of endothelial (eNOS), inducible (iNOS), and neuronal (nNOS) NO synthases, as well as markers of apoptosis, were measured in the IR -and IR + hearts. In the IR + hearts, cardiac function indices (CFI) and the infarct size were also measured. Results: Nitrate increased catalase activity (97%) and eNOS expression (2.94-fold) in the IR -hearts. In the IR + hearts, nitrate reduced left ventricular (LV) end-diastolic pressure (11.6%) and infarct size (26.2%) and increased recovery of LV developed pressure (44.0%) and peak rate of positive (28.9%) and negative (15.4%) changes in LV pressure. In addition, in the IR + hearts, nitrate increased eNOS and B-cell lymphoma-2 (Bcl-2) as well as decreased iNOS, Bcl-2 associated X protein (Bax), caspase-3, caspase-8, caspase-9, and tumor necrosis factor-α (TNF-α) expression. Nitrate increased total antioxidant capacity (TAC) and catalase (CAT) activity and decreased malondialdehyde (MDA) levels at month 9 in serum and IR + hearts. Conclusion: The favorable effects of nitrate against IR injury were associated with higher eNOS and Bcl-2 expression, CAT activity, TAC, and lower iNOS, Bax, caspase-3, caspase-8, caspase-9 and TNF-α expression, and MDA in the heart tissue. Nitrate preconditioning alleviated IR-induced myocardial injury in OVX rats; this effect was associated with eNOS upregulation before IR and the blunting of OVX-induced eNOS downregulation, iNOS upregulation, apoptosis, and oxidative stress in heart tissue after IR.